Problem-based learning quartet cards development assisted by QR code: Critical thinking on environmental change - Damanik, Alfina Sukma Hayati; Rahmadina, Rahmadina (STKIP Persada Khatulistiwa Sintang, 2025)
Conventional biology learning methods make students less active during the learning process. The lack of interactive media also causes students to have difficulty understanding the material, resulting in low critical thinking skills. This study aims to develop a Problem-Based Learning (PBL) based quartet card media assisted by QR codes on the topic of environmental change to improve students’ critical thinking skills. The research method used was Research and Development with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research subjects were 34 students of class X4. The assessment instruments included needs analysis, expert validation sheets, teacher and student response questionnaires, and pretest–posttest evaluations. The results showed that the PBL-based quartet cards assisted by QR codes obtained a validity score of 89% from media experts and 98% from material experts. The quartet cards were also categorized as very practical based on students' responses score of 90% and teachers' responses score of 93%. The N-Gain test obtained a score of 0.76, with a percentage of 76%, which falls into the high category. Therefore, the Problem-Based Learning (PBL) based quartet card media assisted by QR codes is declared valid, practical, and effective for supporting biology learning.